2017
DOI: 10.18488/journal.1/2017.7.2/1.2.140.149
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation in Higher Education: Challenges for Research Collaboration for Academics in Developing Countries (Zimbabwe)

Abstract: Recently, the academic profession has come under great pressure to transform in the way it does in business movingfrom the predominantly collegial to a managerialist model (Kogan and Teichler, 2007). With the advent of managerialism, universities have grown into large bureaucratic structures with professional managers (Kogan and Teichler, 2007).These changes tend to affect academics in certain ways, for example through growing internationalization, change in management style and the aspect of relevance (Kogan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results showed that commitment significantly affects collaborator selection for research collaboration in the university context, and it is consistent with [68]. According to Tarusikirwa and Mafa [142], failure to make commitments often leads to collaboration failure. Thus, this research suggests that the researchers concentrate on commitment as an important factor when selecting their collaborators because committed collaborators will prioritise collaboration tasks.…”
Section: Discussionsupporting
confidence: 64%
“…The results showed that commitment significantly affects collaborator selection for research collaboration in the university context, and it is consistent with [68]. According to Tarusikirwa and Mafa [142], failure to make commitments often leads to collaboration failure. Thus, this research suggests that the researchers concentrate on commitment as an important factor when selecting their collaborators because committed collaborators will prioritise collaboration tasks.…”
Section: Discussionsupporting
confidence: 64%
“…Some foreign partnerships in the higher education sector, which do not have equal benefits and experience, suffer from the lack of expertise, recognition, and uncertain jurisdiction of each party (Jiang and Carpenter 2014). Researchers have analysed inequalities in various parameters like expertise in institutional research, infrastructure, incentives for scholarships, and disparities in work habits as some of the major constraints for fruitful institutional collaborations between African universities with U.S. partners (Semali, Baker, and Freer 2013;Tarusikirwa and Mafa 2017). In Middle East and South East Asia, some of the off-shore campuses of foreign universities are facing difficulties in sustaining (Lane 2011).…”
Section: Recent Developments On Policies and Strategiesmentioning
confidence: 99%
“…These challenges are personal, institutional, and systemic. For instance, at a continental level compared to the Western countries, universities in Zambia, Uganda, Kenya, Ghana, Tanzania, and a host of other African countries confront many challenges (Tarusikirwa & Mafa 2017;Mushemeza 2016;Alemu, et al 2010). This speaks to a general malaise evident in Africa's higher education sector.…”
Section: Introductionmentioning
confidence: 99%